2015
DOI: 10.5817/cp2015-2-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Facebook attachment and obsessive-compulsive disorder severity

Abstract: Despite the widespread use of social networking sites (SNS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 39 publications
5
17
0
Order By: Relevance
“…Research in the field of social media and mental health has largely focused on the potential harm of social media engagement. For example, researchers have observed or empirically evidenced associations between social media use and the occurrence and exacerbation of experiences associated with psychosis [ 5 - 7 ], mood disorders [ 8 - 10 ] personality disorders [ 10 ], eating disorders [ 11 , 12 ], and obsessive compulsive disorder [ 13 ]. However, others have reported that there are no associations between mental health problems and social media use and, in some cases, significant improvements in social functioning have been observed following social media engagement [ 14 - 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research in the field of social media and mental health has largely focused on the potential harm of social media engagement. For example, researchers have observed or empirically evidenced associations between social media use and the occurrence and exacerbation of experiences associated with psychosis [ 5 - 7 ], mood disorders [ 8 - 10 ] personality disorders [ 10 ], eating disorders [ 11 , 12 ], and obsessive compulsive disorder [ 13 ]. However, others have reported that there are no associations between mental health problems and social media use and, in some cases, significant improvements in social functioning have been observed following social media engagement [ 14 - 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has even been claimed that epigenetic mechanisms may come into play here, leading to an atrophying of our powers of memory and a reduction of our attention span; we are also negatively impacted by the demands of engagement in multitasking, icon-based communication, and extensive possibilities for psychological disturbance, with Internet Addiction Disorder (IAD) becoming a recognized mental problem. All these consequences of the intensive use of digital technology reinforce the need for the scientific investigation of what happens to Internet users following such a massive insertion of digital technology into their lives [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Social media, operationalized as the total time spent per day, visits per day and global frequency of visits on social media, was associated with depression in a large sample of U.S. young adults [2 ]. Facebook intrusiveness was correlated with obsessive-compulsive disorder severity and with obsessive beliefs in a sample of young adults (aged 1 -24) [24].…”
Section: Adult Studiesmentioning
confidence: 99%